2023
DOI: 10.1109/access.2023.3324177
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Cybersecurity in Grid-Connected Power Electronics Converters: Vulnerabilities, Countermeasures, and Testbeds

Ruiyun Fu,
Mary E. Lichtenwalner,
Thomas J. Johnson

Abstract: With the increasing installations of solar energy, electric vehicles, and other distributed energy resources and the deeper developments of digitalization and standardization, cybersecurity became more and more essential and critical in modern power systems. Unfortunately, most prior research work focuses on the cybersecurity of power transmission and distribution networks other than distributed energy devices and their grid-connected power converters. Focusing on the Grid-Connected Power Electronics Converter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 72 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…In [28], the authors provide an in-depth literature review of the vulnerabilities, countermeasures, and test environments associated with Grid-Connected Power Electronics Converters (GCPECs). From the review and the analysis, it is found that GCPEC vulnerabilities include both cyber and physical layers that are easily accessible to malicious hackers.…”
Section: Related Workmentioning
confidence: 99%
“…In [28], the authors provide an in-depth literature review of the vulnerabilities, countermeasures, and test environments associated with Grid-Connected Power Electronics Converters (GCPECs). From the review and the analysis, it is found that GCPEC vulnerabilities include both cyber and physical layers that are easily accessible to malicious hackers.…”
Section: Related Workmentioning
confidence: 99%